Some Properties of Cyclotic Graph - U. M. Prajapati; S. K. Singh (International Journal of Mathematics And its Applications, 2016)
In the present work we have introduced a new graph called Cyclotic graph $G(n,k)$. We have given many examples of Cyclotic graph $G(n,k)$. We have proved some results about connectedness, planarity, regularity and number of edges in Cyclotic graph. We have also proved that $G(n,k)$ is not Eulerian graph and found some results which shows when $G(n,k)$ is bipartite and Hamiltonian.